2013
DOI: 10.3171/2012.10.jns12518
|View full text |Cite
|
Sign up to set email alerts
|

Association of a higher density of specialist neuroscience providers with fewer deaths from stroke in the United States population

Abstract: Object. Stroke is a leading cause of death and disability. Given that neurologists and neurosurgeons have special expertise in this area, the authors hypothesized that the density of neuroscience providers is associated with reduced mortality rates from stroke across US counties.Methods. This is a retrospective review of the Area Resource File 2009-2010, a national county-level health information database maintained by the US Department of Health and Human Services. The primary outcome variable was the 3-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
(49 reference statements)
0
14
1
Order By: Relevance
“…5 Although the American Stroke Association does not explicitly mandate that a neurologist be the sole provider of care to patients with acute stroke, best practices indicate that VNs should play the leading role in stroke units. [9][10][11] The American Board of Psychiatry and Neurology began certifying VNs in the United States in 2005 as a way to formally recognize those who completed special training and who demonstrate competence in all aspects of vascular neurology care. 12 The background of those VNs is diverse.…”
Section: Best Practices For Stroke Carementioning
confidence: 99%
“…5 Although the American Stroke Association does not explicitly mandate that a neurologist be the sole provider of care to patients with acute stroke, best practices indicate that VNs should play the leading role in stroke units. [9][10][11] The American Board of Psychiatry and Neurology began certifying VNs in the United States in 2005 as a way to formally recognize those who completed special training and who demonstrate competence in all aspects of vascular neurology care. 12 The background of those VNs is diverse.…”
Section: Best Practices For Stroke Carementioning
confidence: 99%
“…9,10 Additionally, several studies in other specialties have shown relationships between regional density of healthcare providers and outcomes. Regions with a higher density of primary care physicians have a lower mortality for ambulatory care–sensitive conditions; 11 regions with a higher density of neurologists and neurosurgeons have a lower stroke mortality; 12 and regions with a higher density of gastroenterologists have lower rates of end-stage colorectal cancer. 13 However, the relationship between density of cardiologists and outcomes for cardiac conditions such as AMI and HF is unknown.…”
mentioning
confidence: 99%
“…The most powerful result reported by Desai et al 6 is the much higher stroke-related mortality for rural residents. Stroke is a time-sensitive disease, and for many US residents it is inevitable that the nearest hospital will lack sophisticated stroke care: most US towns smaller than 30,000 residents have no neurosurgeon, and most smaller than 20,000 have no neurologist.…”
mentioning
confidence: 88%
“…Stroke incidence and mortality rates in the US are well known to have substantial geographic variation, some of which is explained by demographic characteristics-the level of stroke risk factors in the resident population, such as smoking, obesity, and other cardiovascular risk factors. Desai and colleagues 6 used the US Department of Health and Human Services Area Resource File (ARF) to investigate the number of specialist and generalist physicians practicing in US counties as a predictor of stroke-related mortality in the resident population from 2004 to 2006. The investigators report a lower risk of death from stroke in counties with a higher density of neuroscience providers (neurologists and neurosurgeons), with 1 less death per million population per year for every 3 more neuroscience providers practicing in a county.…”
mentioning
confidence: 99%
See 1 more Smart Citation